A cluster randomised controlled trial evaluating an incentive‐based outdoor physical activity programme to increase outdoor time and prevent myopia in children. (27th January 2014) - Ngo, Cheryl S.; Pan, Chen‐Wei; Finkelstein, Eric A.; Lee, Chun‐Fan; Wong, Inez B.; Ong, Julia; Ang, Marcus; Wong, Tien‐Yin; Saw, Seang‐Mei
Abstract Purpose To evaluate an incentive‐based intervention to increase time spent outdoors among children in a 9‐month cluster randomised controlled trial. Methods Two hundred and eighty‐five children aged 6–12 years of age were randomised to the intervention (n = 147) or control arm (n = 138) in the Family incentive trial (FIT). The FIT intervention comprised of targeted education on myopia and good eye care habits, structured weekend outdoor activities and incentives for children to increase their daily steps via pedometers. The main outcome measure was outdoor time, measured by the WHO questionnaire and a 1‐week diary. Results Interim analysis at 6 months showed a significant increase in mean outdoor time per week in the intervention arm (14.75 h week−1) compared to the control arm (12.40 h week−1) as measured by the questionnaire (p = 0.04). However, greater outdoor time was not statistically significant at the end of the trial (15.95 h week−1 vs 14.34 h in the control group (p = 0.29). Conclusions There was an increase in outdoor time for children in the incentive‐based physical activity outdoor program after 6 months but not at the end of the trial. Further larger school trials with better compliance with the intervention and longer duration could be conducted to evaluate clinical outcomes such as myopic shifts.